Pieties and gender - Sjørup, Lene; Christensen, Hilda Rømer (International studies in religion and society ;, 2009)
Taking the works of Saba Mahmood on piety and gender as a point of departure, this anthology discusses pieties and politics, methodologies, virtuous masculinities, and symbolic gender representations.